Climatic and anthropogenic drivers of zero-flow events in intermittent rivers in Poland - Agnieszka Rutkowska; Marzena Osuch; Mirosław Żelazny; Kazimierz Banasik; Mariusz Klimek (Journal of Water and Land Development, 2023)
River intermittence was studied based on data from hydrological monitoring in Poland. We screened the entire state database and two another data sources applying the criterion for zero-flow event: discharge less than 0.0005 m 3∙s –1, and found five intermittent rivers with catchment area from 9.2 to 303.7 km 2. We aimed at finding associations between intermittence and climatic driving forces (temperature and precipitation), and between intermittence and anthropogenic activity. We used the Spearman correlation coefficient, circular statistics, and statistical tests for trend. The concentration of zero-flow days, mostly in summer, and the decreasing trend in the standardised precipitation evapotranspiration index ( SPEI) in all catchments at various aggregation levels, and an increasing trend in the total number of zero-flow days and in the maximum length of zero flow events in two rivers, were detected. The strong negative correlation (–0.62 ≤ ρ < 0) between intermittence and the SPEI backward lagged in time showed that intermittence resulted from prolonged deficits in climatic water balance due to increasing evapotranspiration. The reaction of the Noteć catchment, amplified by the anthropogenic pressure (brown coal mines), was reflected in the atypical shape of the rose diagram and in inhomogeneities in river discharges. The results show that the rose diagram can serve as an indicator of the degree of anthropogenic impact on runoff conditions.